The relationship between work safety and health toward employee performance at public work department, Segamat, Johor / Nurul Syahida Zafarulhak - Zafarulhak, Nurul Syahida (2013)
The purpose of this paper is to examine the relationship between work safety and health toward employee performance among administration staff at Public work Department, Segamat, Johor. The scope for this paper was included the whole of administration staff on this organization. For the methods, this paper is based on questionnaire data collected from 50 respondents in that organization. Included in the questionnaire are the demographic factors, work safety and health factors and also employee performance factors. Correlation analysis is used to examine the relationship between variables. In findings, it was found that two variables that measure work safety and health are positively and significantly associated with employee's performance (work practices).